What keeps them kicking the ball? : Young female footballers’ reasons to not to quit - Björn, Kaisa (2018)
Youth sport participation decreases as the age. Research indicates there is a larger decrease noted in females compared to males, particularly in football. The number of youth female players participating in football decreases by half between ages 12 and 14.